The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.physe.2014.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Geometry-induced electron doping in periodic semiconductor nanostructures

Abstract: Recently, new quantum features have been observed and studied in the area of nanostructured layers. Nanograting on the surface of the thin layer imposes additional boundary conditions on the electron wave function and induces G-doping or geometry doping. Gdoping is equivalent to donor doping from the point of view of the increase in electron concentration n. However, there are no ionized impurities. This preserves charge carrier scattering to the intrinsic semiconductor level and increases carrier mobility wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…Present developments in nanotechnology enable patterning of semiconductor layers in to gratings with periods much smaller than 1 μm . In our previous works, we have made such structures in Si layers . We have shown that these so‐called nanogratings (NGs) exhibit strongly modified electronic, thermoelectric, optical, and electron emission properties, if their sizes becomes comparable to de Broglie wavelength of electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Present developments in nanotechnology enable patterning of semiconductor layers in to gratings with periods much smaller than 1 μm . In our previous works, we have made such structures in Si layers . We have shown that these so‐called nanogratings (NGs) exhibit strongly modified electronic, thermoelectric, optical, and electron emission properties, if their sizes becomes comparable to de Broglie wavelength of electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, NG introduction profoundly changes photoluminescence properties of Si above the energy gap. In the light of the works by Tavkhelidze et al [5][6][7][8] the observed changes can plausibly be explained by G-doping effect. At the same time, along with metallization due to G-doping, involvement of surface plasmons or, more exactly, plasmon polaritons is possible and can additionally be considered to account for the observed photoluminescence emerging above the energy gap of Si.…”
Section: Sample Preparation and Characterizationmentioning
confidence: 75%
“…We used saturated value of the ratio to estimate phonon gas temperature that is found from the relation I aÀst =I St ¼ expðÀ hv=K B TÞ [18]. According to our estimations, the drop (if any) in the temperature of phonons, expected in the case of G-doping [5] does not exceed 3 K below the ambient temperature (3K). However, more Raman observations, especially for Raman spectra taken with excitation energies from transparency region of Si (i.e., below the energy gap) are necessary to come to a definite conclusion.…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Introduction Noticeable metallization of semiconductor thin layers with nano-grating has recently been disclosed and accounted for the increased number of conduction electrons due to depression of the occupied quantum states in the systems with nano-grating [1,2]. It is important to mention that above increase in conduction electron concentration, or so-called geometry-induced doping (G-doping) results from re-arrangement in electron eigenstates.…”
mentioning
confidence: 99%